Minimal Hereditary ω-Local Non-ℌ-Formations - Sel’kin, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We describe minimal hereditary ω-local non-ℌ-formations, where ℌ is a formation of the classical type.